Teachers' Challenges During COVID-19 - Manullang, Tryastuti Irawati Belliny; Rochyadi, Endang; Sunardi, Sunardi; Suryadi, Ace; Haerudin, Dingding (Indonesian Journal of Disability Studies, 2022)
The existence of COVID-19 in Indonesia was officially announced by the president in March 2020 before the virus emerged in Wuhan China. School closure was conducted and the policy of distant learning was officially released by the Ministry of Education. This research aimed to find the challenges that teachers in Indonesia encountered during the COVID-19 pandemic outbreak and how teachers overcome the learning process challenges. The study was conducted towards primary school teachers in some provinces in Indonesia through an online survey with close-ended and open- ended questions. Our research findings showed teachers encounter challenges that include the disturbance in teaching and learning regarding accessibility, learning quality, school-home relationship, and technology awareness. Teachers also changed their ways of teaching by sending the learning materials via Google Classroom, WhatsApp (cross-platform messaging), and a few still conducted face-to- face meetings with strict policies.